PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (SURVEI PADA PERUSAHAAN YANG TERMASUK DALAM INDEKS SRI KEHATI) - H. Akram; Animah Animah; Prayitno Basuki (Jurnal Aplikasi Akuntansi, 2017)
The objective of this study is to examine the influence of corporate governance mechanism on the disclosure of CSR. Studies conducted on the companies included in the SRI KEHATI index during 2011-2014. The study obtained 18 companies as sample of this study. The results of multiple linear regression analysis showed that the audit committee and independent commissioner have no influence on the disclosure of CSR, while institutional ownership was found to have influence on the disclosure of CSR. The study implies that the stakeholders are able to change the dimensions of CSR implementation, whereby previously it was only for humanitarian and environmental aspects, CSR is now able to increase its profit and finally the goal to sustainability can be manifested